PERILAKU KADER KESEHATAN DALAM DIGITALISASI PENCATATAN ANTENATAL CARE DI KELURAHAN PALUMBONSARI, KAWASAN TIMUR KARAWANG (Berita Kedokteran Masyarakat (BKM), 2019)
Behavior of health volunteer in digitalization of antenatal care recording in Kelurahan Palumbonsari, Timur KarawangPurpose: This study was aimed to determine the behavior of health volunteers in digitizing antenatal records in Palumbonsari Village, Karawang Timur Regency. Method: This research was quantitative research. This research was in July 2018. The technique of collecting data used a questionnaire. The population in this study was health volunteers in the East Karawang Health Center. Palumbonsari. The sampling method was purposive sampling totaling 32 health volunteers. Results: The results of the study of 32 respondents, 75% of respondents had a good level of knowledge about digitizing antenatal care records, 78.12% who had sufficient attitudes and levels of respondent behavior were 75% ready to support the implementation of digitizing antenatal care records. Conclusion: The behavior of health cadres in digitizing antenatal care records in Palumbonsari Village was quite good. It was recommended that all health services be able to carry out digitalization of antenatal care records in an effort to record and store medical records of pregnant women which were more accessible at any time and anywhere.